230k views
6 votes
Solve the equation below

Solve the equation below-example-1

2 Answers

9 votes
Answer is x = -1 and y = -1

When substituting the second equation into the first equation for y we can solve for x

-x - 2 = 9x + 8

-x = 9x + 10

-10x = 10

x = -1

Then we can plug x back into one of our original equations to find y

y = 9(-1) + 8

y = -9 + 8

y = -1
User Fluminis
by
4.6k points
3 votes

Answer:

(-1,-1)

Explanation:

y = 9x + 8 and y = -x - 2

then 9x + 8 = -x - 2

9x + x = -8 - 2

10x = -10

x = -1

y = -x - 2 = - (-1) - 2 = 1 - 2 = -1

User Green Acorn
by
5.1k points